Targeting adenosine A2A receptor antagonism for treatment of cancer. (2nd November 2018) - Congreve, Miles; Brown, Giles A.; Borodovsky, Alexandra; Lamb, Michelle L.
ABSTRACT: Introduction : Adenosine A2A Receptor (A2A R) antagonists are an emerging class of agents that treat cancers, both as a monotherapy and in combination with other therapeutic agents. Several studies support the accumulation of extracellular adenosine in the tumor microenvironment as a critical mechanism in immune evasion implicating A2A R antagonists for use in immuno-oncology. Areas covered : In this perspective article, the authors briefly outline the history of the A2A R antagonist field for central nervous system indications and give their perspective on the status of agents progressing today in oncology. A brief description of the biological rationale in oncology is given. A particular focus of this article is progress in A2A R structure determination and its impact on Structure-Based Drug Design. Expert opinion : Our understanding of the A2A R antagonist mechanism of action has changed and is now being clinically validated by several key companies in the oncology field. This area is likely to rapidly develop over the next 1–2 years.